BLACK-WATER FORESTS (IGAPÓ) VS. WHITE-WATER FORESTS (VÁRZEA) IN THE AMAZON: FLORISTICS AND PHYSICAL STRUCTURE - Myster, Randall W. (2015)
Flooded forests occur across the landscape of the Amazon basin and, because they are important to our shared human density, need further investigation. Here I use replicated plots to examine the floristics and physical structure of the two most common kinds of flooded forest-types in the Amazon. I set up four 50 m x 50 m forest plots in black-water forest (igapó) in Peru and also in white-water forest (várzea) in Ecuador. I then sampled all trees in all plots at least 10 cm dbh for species, and then generated a variety of floristic and physical parameters. There was species variation among the plots within both forest-types, but little variation in physical structure. The four igapó plots taken together (now 1 ha) had 16 families, 29 genera and 31 species with Fabaceae, the most common family of which also had the most genera and the most species. The four várzea plots taken together (now 1 ha) had 42 families, 91 genera and 159 species, with Fabaceae again the most common family which also had the most genera and the most species. There were only four species in common. In general the várzea plots had more stems, and more large stems (at least 40 cm dbh) than the igapó plots, but mean stem size was very similar. Structural comparison to terra firme 1 ha plots showed it had more stems, thicker stems and more above-ground biomass compared to either of these pooled 1 ha flooded plots. Finally all study plots conformed to the reverse J stem size distribution pattern for all stems.